2023
DOI: 10.3390/v15020312
|View full text |Cite
|
Sign up to set email alerts
|

Omicron Waves in Argentina: Dynamics of SARS-CoV-2 Lineages BA.1, BA.2 and the Emerging BA.2.12.1 and BA.4/BA.5

Abstract: The COVID-19 pandemic has lately been driven by Omicron. This work aimed to study the dynamics of SARS-CoV-2 Omicron lineages during the third and fourth waves of COVID-19 in Argentina. Molecular surveillance was performed on 3431 samples from Argentina, between EW44/2021 and EW31/2022. Sequencing, phylogenetic and phylodynamic analyses were performed. A differential dynamic between the Omicron waves was found. The third wave was associated with lineage BA.1, characterized by a high number of cases, very fast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Compared to the reference sequence hCoV-19/Wuhan/WIV04/2019 (GISAID accession number EPI_ISL_402124), the 1263 genome sequences displayed a total of 1631 amino acid changes in different viral genes (912 in ORF1a/1b, 268 in S, 121 in N, 114 in ORF3a, 94 in ORF7a, 47 in ORF8, 28 in M, 18 in ORF6, 17 in ORF7b, and 12 in E). In the Argentine sequences, all the C.37 lineage defining amino acid changes [ 41 ], shown in grey in Figure 4 A, were found at a frequency higher than 95.9%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the reference sequence hCoV-19/Wuhan/WIV04/2019 (GISAID accession number EPI_ISL_402124), the 1263 genome sequences displayed a total of 1631 amino acid changes in different viral genes (912 in ORF1a/1b, 268 in S, 121 in N, 114 in ORF3a, 94 in ORF7a, 47 in ORF8, 28 in M, 18 in ORF6, 17 in ORF7b, and 12 in E). In the Argentine sequences, all the C.37 lineage defining amino acid changes [ 41 ], shown in grey in Figure 4 A, were found at a frequency higher than 95.9%.…”
Section: Resultsmentioning
confidence: 99%
“…The Lambda variant is characterized by multiple lineage-specific deletions and amino acid substitutions in its viral genome, as shown in Figure 4 A [ 41 ]. Specifically, the spike protein of the Lambda variant has a unique pattern of eight mutations (G75V, T76I, R246N, Δ247-253, L452Q, F490S, D614G, and T859N).…”
Section: Discussionmentioning
confidence: 99%
“…In winter 2021, the BA.1 variant and its subvariants started a new epidemiological surge worldwide. Afterward, BA.2 superseded them as the predominant variant in the world [8,9], allowing the epidemic wave of BA.1 to continue in some countries [10,11], or causing a separate wave in other countries [12,13], or leading to a small number of cases without an associated epidemic wave in others [14,15]. The genomic sequences of BA.1 and BA.2 variants (and their subvariants) differ by 23 amino acids [6], resulting in enhanced replication capacity and transmissibility of BA.2 [9,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in the United States showed that breakthrough infections with Omicron variant were more likely, even in subjects with a booster dose, probably due to immune escape [ 46 ]. Overall, variants found in our study were coincident to the most frequently circulating variants in the community at each time, regardless of the type of vaccine and vaccination status [ 4 , 34 ].…”
Section: Discussionmentioning
confidence: 98%
“…As determined by viral sequencing, the most prevalent variant detected in our study was Delta, followed by Omicron, Gamma and Lambda. Each variant was prevalent in the period of highest circulation in Buenos Aires city and surroundings, according to data from Argentina [ 3 , 4 , 34 ].…”
Section: Discussionmentioning
confidence: 99%